Mast Cells in Alveolar Septa of COVID-19 Patients: A Pathogenic Pathway That May Link Interstitial Edema to Immunothrombosis - Motta Junior, Jarbas da Silva; Miggiolaro, Anna Flavia Ribeiro dos Santos; Nagashima, Seigo; de Paula, Caroline Busatta Vaz; Baena, Cristina Pellegrino; Scharfstein, Julio; de Noronha, Lucia (Frontiers in Immunology, 2020)
It is currently believed that innate immunity is unable to prevent the spread of SARS-CoV-2 from the upper airways to the alveoli of high-risk groups of patients. SARS-CoV-2 replication in ACE-2-expressing pneumocytes can drive the diffuse alveolar injury through the cytokine storm and immunothrombosis by upregulating the transcription of chemokine/cytokines, unlike several other respiratory viruses. Here we report histopathology data obtained in post-mortem lung biopsies of COVID-19, showing the increased density of perivascular and septal mast cells (MCs) and IL-4-expressing cells (n = 6), in contrast to the numbers found in pandemic H1N1-induced pneumonia (n = 10) or Control specimens (n = 10). Noteworthy, COVID-19 lung biopsies showed a higher density of CD117+ cells, suggesting that c-kit positive MCs progenitors were recruited earlier to the alveolar septa. These findings suggest that MC proliferation/differentiation in the alveolar septa might be harnessed by the shift toward IL-4 expression in the inflamed alveolar septa. Future studies may clarify whether the fibrin-dependent generation of the hyaline membrane, processes that require the diffusion of procoagulative plasma factors into the alveolar lumen and the endothelial dysfunction, are preceded by MC-driven formation of interstitial edema in the alveolar septa.